2007
DOI: 10.1093/brain/awm114
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations of ND genes in complex I deficiency associated with mitochondrial encephalopathy

Abstract: Isolated Complex I (CI) deficiency, the most frequent cause of mitochondrial disease, is a clinically and genetically heterogeneous condition. Complex I is a giant multiheteromeric enzyme composed of seven ND subunits encoded by mitochondrial DNA (mtDNA) genes, and at least 38 subunits encoded by nuclear genes. To establish the contribution to human mitochondrial encephalopathy of ND versus nuclear gene mutations, we have been undertaking a systematic analysis of CI genes in a cohort of 46 adult and paediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(108 citation statements)
references
References 28 publications
9
99
0
Order By: Relevance
“…The T10191C mutation, detected in patient 2 in this study, was first reported in a patient that presented with a progressive Leigh-like clinical picture of epilepsy, strokes, optic atrophy and cognitive decline by Taylor et al 32 Subsequently, several MELAS or LS patients were reported carrying the T10191C mutation. 31,[33][34][35] The clinical features of patient 2 in the present study conformed with typical MELAS but her brain MRI showed lesions in both cerebral cortex and midbrain, suggesting that a diagnosis of MELAS/LS overlap syndrome was more appropriate. Patient 3 presented a similar clinical picture as patient 2, with a final diagnosis of MELAS/LS overlap syndrome based on the combination of clinical manifestations and brain MRI findings.…”
Section: Discussionsupporting
confidence: 63%
“…The T10191C mutation, detected in patient 2 in this study, was first reported in a patient that presented with a progressive Leigh-like clinical picture of epilepsy, strokes, optic atrophy and cognitive decline by Taylor et al 32 Subsequently, several MELAS or LS patients were reported carrying the T10191C mutation. 31,[33][34][35] The clinical features of patient 2 in the present study conformed with typical MELAS but her brain MRI showed lesions in both cerebral cortex and midbrain, suggesting that a diagnosis of MELAS/LS overlap syndrome was more appropriate. Patient 3 presented a similar clinical picture as patient 2, with a final diagnosis of MELAS/LS overlap syndrome based on the combination of clinical manifestations and brain MRI findings.…”
Section: Discussionsupporting
confidence: 63%
“…Given the wide variability in the clinical manifestations of complex I deficiency, we investigated whether a correlation between the severity of the clinical phenotype and mutation-specific cellular features could exist. We used a cellular model consisting of primary human skin fibroblasts derived from a cohort of four individuals (Pat#1 (patient 2 in Corona et al 25 ), Pat#2 (patient 8 in Bugiani et al 26 ), Pat#3 (patient 4 in Bugiani et al 26 ), Pat#4 (patient 6 in Malfatti et al 27 )) bearing mutations in the ND5 gene and from three independent healthy individuals as controls (Ctrl#1, Ctrl#2 and Ctrl#3). Pat#1 and Pat#2 are two unrelated patients with the same 13514A4G mutation, displaying atypical MELAS and Leigh syndrome, respectively, Pat#3 is a Leigh patient with a different mutation (13513G4A) and Pat#4 has the 13063G4A mutation and is affected by typical MELAS.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we investigated autophagy and mitochondrial Ca 2+ signaling in human fibroblasts from control subjects and from a set of patients carrying mutations in the mtDNA-encoded ND5 subunit of the ETC complex I. [25][26][27] Despite the impaired complex I activity 25,26 and the increased ROS production (data not shown), these cells do not show any major defects in resting ΔΨ mt (Supplementary Figure S5c) or in organelle morphology (Figures 4d and e). However, we observed a marked increase of the autophagic flux in fibroblasts carrying the 13514A4G mutation (Figures 1a-d and Supplementary Figures S1a-d).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 80% of patients have a mutation, Adenine to Guanine transition at the tRNA for Leucine at position 3243 in the mtDNA (Goto et al, 1990). There are other genotypic etiologies of MELAS involving other mitochondrial DNA mutations as well as nuclear DNA mutations (Malfatti et al, 2007;Janssen et al, 2006). Age of onset varies but most all patients present before 40 years of age.…”
Section: Mitochondrial Myopathy Encephalopathy Lactic Acidosis Andmentioning
confidence: 99%